Vegetative Propagation of Albizia amara through Stem Cuttings and Biochemical Status during Rooting - Handa, A.K.; Khare, N.; Chauhan, S.P.S. (Indian Journal of Agroforestry, 2020)
Albizia amara is one of the species used widely in different agroforestry systems in the semi arid region particularly under silvipastoral systems. The present investigation revealed that IBA was more effective compared to NAA in inducing rooting in the stem cuttings of this species. The best treatment for inducing rooting was IBA 200 ppm. The biochemical status of the stem cuttings during different stages of rooting play an important role in the success rate for that species. The C/N ratio is very crucial factor in initial stages and higher the ratio higher is the success rate. The total sugar reduced with the rooting as it was utilized as a source of energy during root initiation.